1986
DOI: 10.1046/j.1537-2995.1986.26486262752.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial sepsis secondary to platelet transfusion: an adverse effect of extended storage at room temperature

Abstract: In a 3-month period four episodes of bacterial sepsis related to contaminated random donor platelet concentrates were observed. Evaluation incriminated extended (5 or more days) platelet storage. To determine if platelets stored for longer periods were likely to have greater bacterial contamination, platelet concentrates were inoculated with bacteria and daily quantitative bacteriology was performed. In vitro studies using polyolefin bags indicated contamination could occur with a single organism of Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 7 publications
2
61
0
2
Order By: Relevance
“…On the other hand CNSC is a well-recognized cause of infections in granulocytopenic patients [37, 38]. As infections and septicemia due to transfusion of standard blood products contaminated by CNSC have been described, some authors suggested to discard contaminated hematopoietic autografts [39, 40, 41, 42, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand CNSC is a well-recognized cause of infections in granulocytopenic patients [37, 38]. As infections and septicemia due to transfusion of standard blood products contaminated by CNSC have been described, some authors suggested to discard contaminated hematopoietic autografts [39, 40, 41, 42, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…This combination of storage container, agitation, preservative solution, temperature, and the use of approximately 50 mL of plasma permits satisfactory preservation of platelets for up to 7 days 23,24 However, several instances of bacterial contamination of PCs stored for this period have been reported 25,26 and the storage time from collection to transfusion is is now limited to 5 days. 27 Because several units of PC are pooled to obtain a dose for one transfusion, one reason to use single-donor apheresis platelets is to minimize the number of donors to which the patient is exposed and, theoretically, to minimize the likelihood of disease transmission.…”
Section: Prophylactic Platelet Transfusionsmentioning
confidence: 99%
“…This damage essentially prevents the in vivo 'survival' of platelets [32]. Moreover, storage times have already been reduced from 7 to 5 days based on study results documenting that bacteria can rapidly proliferate under these conditions [33]. While further decreases in storage time may decrease bacterial infections, they will also adversely limit and impact the blood supply [34].…”
Section: Bacterial Infectionsmentioning
confidence: 99%